Association of innate immune IFIH1 gene polymorphisms with dilated cardiomyopathy in a Chinese population. (October 2014) - Dou, Qingyu; Peng, Ying; Zhou, Bin; Lin, Jing; Li, Yajiao; Yang, Hao; Xie, Qiu; Li, Chunmei; Zhang, Lin; Rao, Li
<x xml:space="preserve">Abstract</x> The interferon-induced helicase C domain-containing protein 1 (IFIH1) is a cytosolic RNA sensor belonging to the pattern-recognition receptor (PPR) family. Activation of PPRs on innate immune cells is widely believed to control the development of virus-induced autoimmunity in myocarditis and subsequent dilated cardiomyopathy (DCM). We conducted a pilot study to test whether single nucleotide polymorphisms (SNPs) in IFIH1 were associated with the risk and prognosis of DCM. The TaqMan SNP Genotyping Assay was used to genotype rs1990760 and rs3747517 in 351 DCM patients and 359 controls. The frequency of T allele and CT/TT genotypes at rs1990760 were significantly increased in DCM patients compared to control subjects (p = 0.046 and p = 0.027, respectively). The CC homozygosity was associated with worse prognosis expressed by the endpoint of cardiac death compared with allele T carriers of rs3747517 in both univariable (p = 0.04) and multivariable survival analysis after adjusting for age, sex, left ventricular end-diastolic diameter and ejection fraction (p = 0.01). The results revealed that rs1990760 was associated with susceptibility to DCM and rs3747517 played a role in the prognostic assessment of DCM, reflecting the distinct genetic contributions of innate IFIH1 polymorphisms in controlling the onset and outcome of DCM.